Enhancement of Friction Stir Welding (FSW) Settings for Microstructural Assessment and Mechanical Characteristics on Aluminium 6082 and Copper Joints - B. Lalit Kumar; Dr. Vikash Gadpale (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Aluminium and its alloys are the major material that is used in today’s world. Aluminium alloys are alloys in which Aluminium (Al) is the predominant metal. The typical alloying elements are copper, magnesium, manganese, silicon and zinc. Among the various available Al alloys Al6082 exhibits the properties like low weight, High strength to mass ratio, Weldability etc. Copper and its alloys are widely used in industrial applications due to their excellent electrical and thermal conductivities, good strength, and corrosion and fatigue resistances. The joints of dissimilar materials are widely used in industrial applications due to their technical and beneficial advantages. Aluminium and copper are two common metals in the electric power industry due to unique performances such as higher electrical conductivity, heat conductivity, corrosion resistance and mechanical properties. During FSW process, the material undergoes intense plastic deformation at elevated temperature, resulting in generation of fine and equiaxed recrystallized grains. The fine microstructure in friction stir welds produces good mechanical properties. In this study, the effect of different process parameters in dissimilar FSW of Al6082 alloy and copper, since dissimilar welding of Al6082 and pure copper is rarely explored. The optimized process parameters are utilized to developed different welds of Al6082 alloy and copper and mechanical behaviour of the same are studied by conducting hardness, bending and tensile tests.